Sub-national assessment of aid effectiveness: A case study of post-conflict districts in Uganda - Freddie Ssengooba; Justine Namakula; Vincent Kawooya; Suzanne Fustukian (BMC, 2017)
Abstract Background In post-conflict settings, many state and non-state actors interact at the sub-national levels in rebuilding health systems by providing funds, delivering vital interventions and building capacity of local governments to shoulder their roles. Aid relationships among actors at sub-national level represent a vital lever for health system development. This study was undertaken to assess the aid-effectiveness in post-conflict districts of northern Uganda. Method This was a three district cross sectional study conducted from January to April 2013. A two stage snowball approach used to construct a relational-network for each district. Managers of organizations (ego) involved service delivery were interviewed and asked to list the external organizations (alters) that contribute to three key services. For each inter-organizational relationship (tie) a custom-made tool designed to reflect the aid-effectiveness in the Paris Declaration was used. Results Three hundred eighty four relational ties between the organizations were generated from a total of 85 organizations interviewed. Satisfaction with aid relationships was mostly determined by 1) the extent ego was able to negotiate own priorities, 2) ego's awareness of expected results, and 3) provision of feedback about ego's performance. Respectively, the B coefficients were 16%, 38% and 19%. Disaggregated analysis show that satisfaction of fund-holders was also determined by addressing own priorities (30%), while provider satisfaction was mostly determined by awareness of expected results (66%) and feedback on performance (23%). All results were significant at p-value of 0.05. Overall, the regression models in these analyses accounted for 44% to 62% of the findings. Conclusion Sub-national assessment of aid effectiveness is feasible with indicators adapted from the global parameters. These findings illustrate the focus on "results" domain and less on "ownership" and "resourcing" domains. The capacity and space for sub-national level authorities to negotiate local priorities requires more attention especially for health system development in post-conflict settings.